Bid rigging or collusive tendering: What, when and how is a hard core cartel produced under this mode? - Chang Tokushima, Juan Santiago (2022)
In the last couple of years, the National Institute for the Defense of Competition and the Protection of Intellectual Property has focused its efforts on the persecution and sanction of horizontal practices, initiating a substantial step in favor of improving free market competition.This paper analyses the reasons why public bid riggings are considered per se illegal conducts by our national legislation, as well as how the National Institute for the Defense of Competition and the Protection of Intellectual Property has prosecuted and sanctioned these practices. The authors consider that classifying bid riggings as per se illegal is a consequence of their social impact, since there aren’t any economic reasonsthat differentiate them from other per se illegal conducts.